Liriopogons (Genera Ophiopogon and Liriope, Asparagaceae): A Critical Review of the Phytochemical and Pharmacological Research - Lei, Feiyi; Weckerle, Caroline S.; Heinrich, Michael (Frontiers in Pharmacology, 2021)
The closely related genera Liriope and Ophiopogon (Asparagaceae), collectively known in English as liriopogons, have similar therapeutic uses in treating cough, rheumatoid arthritis, and cleaning heat. The main aim of this review is to understand the current phytochemical and pharmacological knowledge including an assessment of the quality of the scientific evidence. A literature search was conducted in line with PRISMA guidelines, by retrieving available information up to 2020 from five online resources. The bioactive metabolites of liriopogons include steroidal saponins, flavonoids, polysaccharides, organic acids, phenols. Cardiovascular protective, anti-inflammatory, anti-diabetic, anti-oxidant, anti-cancer, neuroprotective, anti-viral, anti-acute myeloid leukemia and hepatoprotective effects have been at the center of attention. From a toxicological perspective Ophiopogon japonicus seems to be safe. Some problems with the quality of the pharmacological evidence stand out including the application of excessive dose level and methodological problems in the design. Additionally, a reasonable link between local/traditional uses and pharmacological assessment is often vague or not reflected in the text. Future researches on liriopogons are required to use rigorous scientific approaches in research on evidence-based natural products for the future benefits of patients.